Side Grafting of Unproductive Cocoa : Socio-Economic and Ecological Impact - Taryono; Dyah Weny Respatie (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2013)
ABSTRACTCocoa is a tree of the humid lowland tropics produced largely by small farmers, therefore in developing countries it can be used to generate farmer’s income, provide labor employment and conserve environment. At the last decade, the cocoa productivity, the size and quality of beans in Indonesia significantly tend to decline due to the ageing of the tree, poor farming maintenance practice, planting of low yielding variety and ravages caused by pest and diseases. Such declining affects the price and the farmer’s income, and farmers respond by leaving the plantation, replacing with food crops or oil palm, and increasing forest clearing which will threaten the environment. Such problem can be addressed by increasing the long term cocoa productivity of existing farms through side grafting of unproductive cocoa trees with genetically improved varieties. In 2008, it was reported that there are around 235.000 ha of unproductive cocoa that can be improved though side grafting. There was almost 90.000 ha that has been side grafted in 2009 and 2010 by the government support, and in 2011 evaluation through focus group discussion has been carried out. Side grafting with recommended varieties normalizes the cocoa growth, and cures the diseases. With a recommended cultivation technique, the productivity increases twice which followed by improve seed size. These result probably will gives an impact not only on the income but also farmer’s future. Several farmers informed that they will not demolish their cocoa farm or even clear new land for crop food. Normal growth of cocoa and stopping opening new land will have a positive effect to the environment especially in mitigating climate change. Keywords: side grafting, cocoa